Systematic review of bovine and zoonotic tuberculosis in the Western Pacific and the Southeast Asia regions of the World Health Organization - Singh, Balbir B.; Dhand, Navneet K.; Cadmus, Simeon; Dean, Anna S.; Merle, Corinne S. (Frontiers in Public Health, 2024)
Introduction Tuberculosis (TB) remains a leading cause of mortality worldwide. We conducted this systematic review to understand the distribution of bovine and zoonotic tuberculosis in the World Health Organization (WHO)’s Southeast Asia Region (SEAR) and Western Pacific Region (WPR) to inform our understanding of the risk posed by this disease. Methods A two-pronged strategy was used by evaluating data from peer-reviewed literature and official reports. A systematic search was conducted using a structured query in four databases (Web of Science, Scopus, Medline, and PubMed) to identify any reports of the occurrence of zoonotic TB. No language and time constraints were used during the search, but non-English language articles were later excluded. The official data were sourced from the World Organization for Animal Health’s (WOAH) World Animal Health Information System (WAHIS) and WHO’s global TB database. Results The retrieved records from SEAR and WPR (n = 113) were screened for eligibility, and data about disease occurrence were extracted and tabulated. In SEAR, all of the five studies that conducted Mycobacterium speciation (5/6) in humans were from India, and the reported Mycobacterium species included M. tuberculosis, M. bovis, M. scrofulacium, M. kansasii, M. phlei, M. smegmatis and M. orygis. In WPR, Mycobacterium speciation investigations in humans were conducted in Australia (8), China (2), Japan (2), NewZealand (2) and Malaysia (1), and the reported Mycobacterium species included M. bovis, M. africanum and M. tuberculosis. Seven countries in WHO’s SEAR have officially reported the occurrence of Mycobacterium bovis in their animals: Bangladesh, India, Indonesia, Myanmar, Nepal, Sri Lanka and Thailand. In WPR, the WAHIS information system includes reports of the identification of M. bovis from 11 countries – China, Fiji, Japan, Malaysia, Mongolia, New Zealand, the Philippines, the Republic of Korea, Singapore, Tonga and Viet Nam. In contrast, human zoonotic TB cases in the WHO database were only listed from Australia, Brunei Darussalam and Palau countries. Discussion The available data suggests under-reporting of zoonotic TB in the regions. Efforts are required to strengthen zoonotic TB surveillance systems from both animal and human health sides to better understand the impact of zoonotic TB in order to take appropriate action to achieve the goal of ending the TB epidemic.